2017
DOI: 10.1515/bjdm-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the stability of dental implants: The concept of osseodensification

Abstract: SUMMARY One of the most important factors that affect osseointegration is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…Additionally, Trisi et al 5 have shown that OD allows the use of wider implants diameters in narrow edentulous ridges, with consequent increase in bone volume. This increase in bone was later shown to reach 30% of the original ridge dimensions by Podaropoulos 6 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, Trisi et al 5 have shown that OD allows the use of wider implants diameters in narrow edentulous ridges, with consequent increase in bone volume. This increase in bone was later shown to reach 30% of the original ridge dimensions by Podaropoulos 6 .…”
Section: Discussionmentioning
confidence: 91%
“…Osseodensification (OD) burs, working in a non-subtractive fashion, condense the implant osteotomy soft bone in lateral direction, leading to a greater bone volume and density, an increase in the bone implant contact, with subsequent increase in insertion torque levels, and reduction in micromotion 26 . However, it has been claimed that OD increases the implant bone bed density, but does not improve implant primary stability 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we analyzed the osseodensification technique operating in the opposite rotatory direction than the conventional drills due to the use of different drills with an exclusive and patented design. Because of this technique, it is possible the bone condensing toward the osteotomy walls within the same surgery moment of the implant site preparation [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…15 Additionally, it was shown that the use of Densah bur allows the insertion of wider implants diameters in narrow edentulous ridges, with consequent increase in bone volume to reach 30% of the original ridge dimensions . 16 Thus the Densah bur has the advantages of expanders combined with the high speed of standard drills and their tactile control. The drilling process using Densah burs can be either clockwise (CW) or counterclockwise (CCW) and is performed at high speeds 800-1500 rpm.…”
Section: Discussion Of Methodologymentioning
confidence: 99%